Performance analysis and optimization of wavelength routed (WR) and wavelength selected (WS) hybrid optical distributed network (ODN) for next generation passive optical network stage 2 (NG-PON2). (October 2018) - Kachhatiya, Vivek; Prince, Shanthi
Graphical abstract: Highlights: Hybrid ODN based NG-PON2 architecture is designed and analyzed using OptiSystem. Fiber nonlinearities abated for multi-wavelength NG-PON2 by optimizing launch power. Performance of NG-PON2 in terms of Q-factor is maximized by optimizing launch power. The number of error free users of NG-PON2 is maximized by optimizing launch power. Range of launch powers are charted for NG-PON2 to maximize the users & performance. Abstract: Next-generation passive optical network stage 2 (NG-PON2) supports the wavelength routed optical distributed network (WR-ODN), power splitter optical distributed network or wavelength-selected optical distributed network (WS-ODN) and hybrid of both the architecture configuration. NG-PON2 is world's first multi-wavelength passive optical network (PON) standard. The fiber dispersion and nonlinearity degrades the performance of NG-PON2 severely. Fiber nonlinearity depends on the optical launch power and fiber reach. This paper focuses on maximizing the network performance and maximizing the number of simultaneous users with error-free performance by optimizing the optical launch power respectively at dynamic reach and differential reach. The optical launch power is optimized to abate the fiber nonlinearity and significantly enhances the performance of NG-PON2 at dynamic fiber reach for Alcatel 6912 Teralight Ultra 1625 commercial fiber specification. Furthermore, precise values of the optimum launch power for the dynamic fiber reach, for different NG-PON2 architecture, under industrial fiber specification is meticulously obtained. It is identified that irrespective of both, WR-ODN and WS-ODN architecture configuration, optimum launch power remains constant. Power budget is calculated for both, maximizing the performance and maximizing the simultaneous number of users at differential reach and dynamic reach of the NG-PON2.